A Systematic Review of Factors Affecting Students’ Satisfaction with Student Affairs Management System (SAMS) in Private Universities: Insights from Xi’an, China - Yao, Bin; Lee, Khiam Jin (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2023)
This systematic review examines the factors influencing students’ satisfaction with the Student Affairs Management System (SAMS) in private universities in Xi’an, China. It analyzes individual factors (trust, respect for expertise, and student involvement) and organizational factors (institutional support and culture) that impact students’ satisfaction with SAMS. The review also explores students’ perceptions of challenges faced at private higher education institutes (HEIs) in Xi’an. Additionally, it investigates the influence of cross-functional collaboration on the relationship between individual and organizational factors. SAMS service quality is assessed based on attributes such as tangibility, responsiveness, safety, reliability, and empathy. To conduct this review, a systematic approach is employed, involving a comprehensive search and analysis of relevant literature. Various academic databases are searched, and rigorous inclusion and exclusion criteria are applied to select high-quality articles for review. Data extraction and synthesis techniques are utilized to identify key themes, trends, and research gaps. Through this critical evaluation of existing literature, the review contributes to a better understanding of the factors influencing students’ satisfaction with SAMS in private universities in Xi’an. The findings of this review provide valuable insights for policy makers, management experts, and educational institutions aiming to enhance student growth and engagement. The results inform evidence-based decision-making and facilitate the development of strategies and interventions to improve the effectiveness and satisfaction of student affairs management systems in private universities. Furthermore, the review identifies areas for future research, suggesting potential avenues for scholars to further explore this important subject..